Server Side development with Node.js and Koa.js Quick Start Guide: Build robust and scalable web applications with modern JavaScript techniques - Omole, Olayinka (Packt Publishing Limited, 2018)
Build real-world robust web applications and APIs using the modern and expressive Koa Node.js framework.Key FeaturesGet up and running with Koa.js and leverage its power with node.jsGet the most out of Koa Async functions and generatorsCreate real time dynamic serverside apps efficiently with Koa.js Book DescriptionEvery developer wants to build modular and scalable web applications. Modern versions of JavaScript have made this possible in Node.js, and Koa is a Node.js framework that makes it easy. This book is the ideal introduction for JavaScript developers who want to create scalable server side applications using Node.js and Koa.js.The book shows you how Koa can be used to start projects from scratch, register custom and existing middleware, read requests, and send responses to users. We will explore the core concepts in Koa, such as error handling, logging, and request and response handling. We will dive into new concepts in JavaScript development, and see how paradigms such as async/await help with modern Node.js application development.By the end of this book, you will be building robust web applications in Koa using modern development paradigms and techniques of Node.js development.What you will learnCreate a simple server in Node.js and KoaWork with custom middleware in KoaHandle errors in KoaCreate routes, handle requests, and send responses from APIsBuild views and use templates in KoaAuthenticate your application and structure it properly in KoaWho this book is forThis book is for serverside developers and JavaScript developers who want to use Koa.js and Node.js to create fast and real time back end applications.